2006
DOI: 10.1111/j.1365-2958.2006.05446.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the core transmembrane complex of the Legionella Dot/Icm type IV secretion system

Abstract: SummaryType IV secretion systems (T4SS) are utilized by a wide range of Gram negative bacteria to deliver protein and DNA substrates to recipient cells. The best characterized T4SS are the type IVA systems, which exhibit extensive similarity to the Agrobacterium VirB T4SS. In contrast, type IVB secretion systems share almost no sequence homology to the type IVA systems, are composed of approximately twice as many proteins, and remain largely uncharacterized. Type IVB systems include the Dot/ Icm systems found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
182
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(202 citation statements)
references
References 49 publications
12
182
0
8
Order By: Relevance
“…oakridgensis seems to have a very limited set of hosts and replicates significantly slower compared to L. pneumophila Corby. This may be in accordance to the low amount of effector proteins and eukaryote-like proteins (total ~80) identified, when compared to what is known for L. pneumophila (>300 effector proteins) (Vogel et al, 1998;Vincent et al, 2006;Burstein et al, 2009;Hubber et al, 2010). A recent in silico analysis of genome sequences revealed a core set of approximately 107 effector proteins present in L. pneumophila strains (Schroeder et al, 2010).…”
Section: The Dot/icm Secretion System Effector Proteins and Eukaryotsupporting
confidence: 54%
“…oakridgensis seems to have a very limited set of hosts and replicates significantly slower compared to L. pneumophila Corby. This may be in accordance to the low amount of effector proteins and eukaryote-like proteins (total ~80) identified, when compared to what is known for L. pneumophila (>300 effector proteins) (Vogel et al, 1998;Vincent et al, 2006;Burstein et al, 2009;Hubber et al, 2010). A recent in silico analysis of genome sequences revealed a core set of approximately 107 effector proteins present in L. pneumophila strains (Schroeder et al, 2010).…”
Section: The Dot/icm Secretion System Effector Proteins and Eukaryotsupporting
confidence: 54%
“…However, a study by Vincent et al (15,37) indicated that other Dot/Icm component proteins, such as T4SS chaperones IcmS and IcmW, may be equally promising baits for this type of screen. Our bioinformatics approach achieved significant success in predicting C. burnetii type IV substrates, as 26 of 42 predicted candidates were confirmed as Dot/Icm substrates (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…To obtain a more complete inventory of substrates transferred by the Dot/Icm system of C. burnetii, we initiated a study to identify such proteins by dual strategies that combined genetic screenings and bioinformatics analyses. Because a subset of Legionella Dot/ Icm substrates specifically interacts with DotF (5), an important component of the T4SS that localizes to the inner membrane of the bacterium (15). We hypothesized that similar interactions occur between Coxiella T4SS substrates and its DotF protein.…”
mentioning
confidence: 99%
“…The remainder was PE-up and included seven extracellular PE-on proteins (ABC transporter periplasmic-binding protein ArtJ, hypothetical protein Lpg0264, flagellar hook protein FlgK, phospholipase C PlcB, protease/elastase LasB, polysaccharide deacetylase Lpg1993, Lpg2443) (70,(92)(93)(94). The further PE-up extr majorly included 8 proteins without assigned function (Lpg2220, Lpg1647, Lpg1645, Lpg0957, Lpg0301 Lpg1318, Lpg2206, Lpg2246), 5 T2SS substrates (chitinase ChiA, phospholipase A/acyltransferase PlaC, hypothetical protein Lpg0956, Lpg0189, Lpg0264), three Dot/Icm effectors (LegP, Lpg1667, Lpg2443) and Dot/Icm apparatus core complex protein DotC, as well as further (in addition to FlgK) motility-related proteins (FliC, FliD) (26,70,(95)(96)(97). The phase-stable extracellular proteome (42 proteins) included 13 T2SS substrates (phospholipase C PlcA, NttC, endoglucanase CelA, lysophospholipase A PlaA, T2 ribonuclease SrnA, NttB, Lpg1832, SclB, aminopeptidases LapB, LapA, zinc metalloprotease ProA, major acid phosphatase Map, Lpg0873), five Dot/Icm effectors (LegY/GamA which was also detected as T2SS substrate (25), LirB, MavL, LegS, Lpg0041), three proteins involved in carbon and energy metabolism (enolase Eno, thioredoxin reductase TrxB1, xylanase-like protein YjeA), as well as nine functionally unassigned proteins (Fig.…”
Section: Overview Of L Pneumophila E and Pe Soluble Whole Cellmentioning
confidence: 99%